Turkey : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2006)
This report focuses on Observance of Standards and Codes on Fiscal Transparency for Turkey. Turkey has continued to make progress toward meeting the requirements of the fiscal transparency code, in particular through a substantial overhaul of the legal system. The adoption of the Public Financial Management and Control Law (PFMCL) in December 2003 was designed to provide the necessary framework for further reforms. In spite of the progress made, further effort is required before Turkey will fully meet the requirements of the Code.